Perspectives of Psychiatric Investigators and IRB Chairs Regarding Benefits of Psychiatric Genetics Research - Roberts, Laura Weiss (J Psychiatr Res, 2018)
There is hope that psychiatric genetics inquiry will provide important insights into the origins and treatment of mental illness given the burden of these conditions. We sought to examine perspectives of psychiatric genetic investigators regarding the potential benefits of genetic research in general and the potential benefits of genetic research for the diagnosis and treatment of mental illnesses specifically. We compared investigator attitudes with those of chairs of Institutional Review Boards (IRB) entrusted with evaluating the benefits and risks of human research studies. Two groups directly engaged with the conduct and oversight of psychiatric genetic research were examined (psychiatric investigators, n=203; IRB Chairs, n=183). Participants rated 15 survey items regarding current and future benefits of general genetic research, possible benefits of psychiatric genetic research, and the importance to society of genetic vs. non-genetic research examining causes and treatments of illnesses. Investigators and IRB Chairs strongly endorsed the future benefits of general genetic research for society and for the health of individuals; compared to IRB Chairs, Investigators were more positive about these benefits. Even after adjusting for demographic variables, psychiatric genetic investigators were significantly more optimistic about genetic research compared with IRB Chairs. Both groups were moderately optimistic about the possible benefits of genetic research related to mental illness. Greater optimism was seen regarding new or personalized medications for mental illnesses, as well as genetic predictive testing of mental illnesses. Greater precision and circumspection about the potential benefits of psychiatric genetic research is needed.